Consolidation Assessment on Fibric Peat Stabilization by using Palm Oil Fuel Ash (POFA) - Mohd Yunus, Norzahanim; Mohd Khaidir Abu Talib; Siti Nor Hidayah Arifin; Nurshahzani Qasrina Ma’amor (Recent Trends in Civil Engineering and Built Environment, 2026)
The study focuses on understanding and improving fibric peat, a problematic soil with high compressibility, void ratio, and moisture content. Engineers face challenges stabilizing this soil, often using cement, which leads to environmental concerns due to high cement usage. This research explores using Palm Oil Fuel Ash (POFA), an unused waste material with cement-like properties, to stabilize fibric peat. Consolidation experiments were performed on peat samples both before and after being treated with POFA (Palm Oil Fuel Ash) to analyze how the settlement under various loads, spanning from 12.5kPa to 400kPa. Results aim to predict how the soil compresses over time when exposed to varying loads. The use of POFA could potentially reduce reliance on cement for soil stabilization, offering a more environmentally friendly alternative for improving peat soil performance.